The relationship between the company’s value and the tone of the risk-related narratives: The case of Portugal - Oliveira, M. G.; Azevedo, G.; Oliveira, J. (Economies, 2021)
The present study aims to identify the impact of the tone of risk reporting narratives on company market value. The paper uses a sample of 34 Portuguese non-finance companies with shares traded at the Euronext Lisbon stock exchange market. The paper conducts an automated content analysis of the risk reporting narratives included in the risk and risk management sections of the annual reports for 2018 by using the software DICTION 7 (Digitext, Inc., Austin, TX, USA) to retrieve the speech tone. Main findings indicate that the tone category “activity” is associated negatively with the company’s market value. This result shows that investors misprice risk information that incorporates traces of overconfidence, narcissistic self-confidence and heroic leadership. The present study extends prior literature by analyzing the economic incentives of the tone of risk reporting narratives, not yet studied. Findings are both relevant to investors to support their decision-making processes and managers to strategically manage their risk communication tactics and benefit from the advantages emanated from them. Limitations related to the research setting do not undermine the generalization of findings because the automated algorithm provided by DICTION assures the content analysis’s reliability. The sample used corresponds to the population of the Portuguese non-finance listed companies.